2006
DOI: 10.1097/01.cji.0000175489.19314.d2
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 + GM-CSF Microsphere Therapy Induces Eradication of Advanced Spontaneous Tumors in her-2/neu Transgenic Mice But Fails to Achieve Long-Term Cure Due to the Inability to Maintain Effector T-Cell Activity

Abstract: A single intratumoral injection of interleukin-12 and granulocyte-macrophage colony-stimulating factor-encapsulated microspheres induced the regression of advanced spontaneous mammary tumors, suppressed additional tumor development, and enhanced survival in her-2/neu transgenic mice. Posttherapy tumor eradication was dependent on both CD4+ and CD8+ T cells and correlated with the tumor infiltration kinetics of a transient effector T-cell response. Upon long-term monitoring, tumor regression was found to be tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 30 publications
1
40
0
Order By: Relevance
“…It is anticipated that by re-activating the T lymphocytes, these cells will orchestrate a cascade of events that result in the killing of tumor locally and that with the release of tumor antigens from the dead and dying tumor cells there will be an induction of a systemic anti-tumor immunity. This expectation has been confirmed in two animal tumor models [141,142] and several clinical trials have shown that low doses of IL-12 injected locally into tumors show little or no toxicity (reviewed in [143]). An Investigational New Drug (IND) application for a local sustained delivery device for the introduction of IL-12 into tumor nodules has recently been approved by the FDA and a Phase I clinical trial that will address the safety and later the efficacy of this in situ tumor vaccination strategy is to be initiated shortly.…”
Section: Discussionmentioning
confidence: 83%
“…It is anticipated that by re-activating the T lymphocytes, these cells will orchestrate a cascade of events that result in the killing of tumor locally and that with the release of tumor antigens from the dead and dying tumor cells there will be an induction of a systemic anti-tumor immunity. This expectation has been confirmed in two animal tumor models [141,142] and several clinical trials have shown that low doses of IL-12 injected locally into tumors show little or no toxicity (reviewed in [143]). An Investigational New Drug (IND) application for a local sustained delivery device for the introduction of IL-12 into tumor nodules has recently been approved by the FDA and a Phase I clinical trial that will address the safety and later the efficacy of this in situ tumor vaccination strategy is to be initiated shortly.…”
Section: Discussionmentioning
confidence: 83%
“…This same result has been achieved in murine models by the slow release into tissue of IL-12 encapsulated microspheres. 51 We anticipate that similar clinical effects would be induced by intratumoral injection of IL-12 cDNA or IL-12 protein encapsulated microspheres.…”
Section: Discussionmentioning
confidence: 99%
“…However, the co-administration of both GM-CSF and IL-12 resulted in a synergistic increase in tumor-infiltrating effector cells, IFN-Îł production and reduced tumor burden [70]. The combination of GM-CSF and IL-12 has also been applied in several other rodent models, including intracranial glioma [71], transgene-induced spontaneous mammary tumors [72] and metastatic lung and colon cancers [73]. In each of these studies, tumor eradication was dependent upon both T and NK cells and correlated with the infiltration of these cell types into the tumor.…”
Section: Granulocyte-macrophage Colony-stimulating Factor (Gm-csf)/il-12mentioning
confidence: 99%